Service Quality-Based Public Trust at City Resort Police in Indonesia - Chaeruddin, M Awal; Syam, Husain; Akib, Haedar; Haris, Hasnawi (KnE Social Sciences, 2024)
Public trust based on service quality in organizations assumes that high public trust influences people to follow government policies, respect the law, and strengthen democracy and social stability. Conversely, low public trust can influence people to reject government policies, doubt the integrity of government institutions, and weaken democracy and social stability. The results of this research article explain public trust based on the quality of service in the police institution. Data, information, and knowledge regarding the locus of the Makassar City Resort Police (Polrestabes) were obtained through observation, interviews, and focus group discussions. The data were analyzed descriptively-qualitatively. The results of the study found that the quality of digital-based public services implemented in the institutions studied was able to change the image of the people served. A positive image of the community is built from the provision of physical evidence (tangibles) that meets expectations, empathy that underlies the desire to serve (responsiveness), and attention and ethics of moral behavior (assurance) in providing services to build trust (reliability) and positive appreciation as a form of external responsibility (accountability) from institutions to service recipients. The dimensions of the quality of public services are actualized in several main aspects as the basis of public trust in the Indonesian City Police Resort (Kapolrestabes) with high levels of achievement, namely in the dimensions of responsiveness, professionalism, transparency, community involvement, as well as security and justice. The performance of these institutions has an impact on increasing public trust in the Indonesian National Police (Polri), both individually and institutionally. Keywords: public trust, service quality, digitalization, institutional, individual